ANALISIS RESIDU KLORPIRIFOS DALAM SAYURAN KUBIS DENGAN METODE HPLC DI BEBERAPA PASAR TRADISIONAL DI SULAWESI UTARA - Abdon Saiya (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2017)
One type of pesticide that is widely used is a group of organophosphates with chlorpyrifos as the active ingredients, because it has more favorable characteristics such as easy to decompose and short persistence time. However, the use of pesticides in addition to leaving residues that can cause environmental pollution, also cause disruption to human health and inhibit trade. Therefore, it is necessary to monitor the use of pesticides through the fulfillment of the maximum residual limit (MRL) so as to ensure food safety by limiting pesticide residue levels on agricultural products. The purpose of this study was to determine the residual levels of chlorpyrifos in cabbage vegetables with previously optimized and validated HPLC methods. The sample of this research is vegetable cabbage taken from several traditional markets in North Sulawesi. Based on the results of the study, it was found that chlorpyrifos were detected in all samples analyzed, although the levels were still below the specified MRL value. The results of this study can be a consideration for consumers and relevant agencies in North Sulawesi to more frequently monitor and evaluate the existence and use of these compounds.